Development of an intuitive control for robot arm with haptic feedback - Ligutan, Dino Dominic F. (Animo Repository, 2019)
With the increasing bomb related incidents and threat of global terrorism, a need for a more convenient improvised explosive ordnance disposal technology must be developed, especially in life-critical missions. An EOD team needs a more competitive bomb disposal protocol using the available technology to effectively combat these threats to national security. A technology that will deal with these threats as well as effectively reduce casualties can be achieved by deployment of bomb disposal robot units. Existing technologies has yet to improve upon the teleoperation of these units to achieve a better sense of control and its environment (Leonard, 2018). In critical missions that requires careful manipulation of isolating the improvised explosive device, an appropriate control and feedback to the human operator is a must to achieve a less troublesome bomb defusal procedure. A suitable feedback mechanism for object manipulation can be achieved by means of haptic feedback technology. Through haptic feedback technology, the operator will achieve sense of touch of the object being manipulated by means of relaying the forces (Robles-De-La-Torre, 2008) experienced by the remote robotic arm to the operator. The existing controller of a remote robot manipulator for bomb disposal robots is cumbersome to operate and requires a skillful knowledge of control interface itself and the immediate environment of the robot. The complexity of sequence of operations to be performed on a control console in order to operate the remote robot arm is time-consuming compared to an action made by the equivalent human arm motion (Heater, 2017). Furthermore, the console does not provide tactile cues as to the state of object being grasped by the remote robot arm during object manipulation. Unless an appropriate feedback mechanism is deployed, it is very likely for the heavy objects to slip beyond the remote robot arm gripper’s contact surfaces without being noticed by the human operator. With the problem mentioned at hand, this study aims to reduce the time needed to operate as well as provide to the human operator a sense of touch of object being grasped by the remote robot arm by developing an intuitive control interface using haptic feedback technology.